Nonviolence in political theory - Atack, Iain (Edinburgh University Press, 2012)
Examines the relevance of nonviolent tactics to current debates about political action and political thought. Nonviolent political action has played a significant role in achieving social and political change in the last century. Mahatma Gandhi and Martin Luther King were prominent proponents of nonviolence. Nonviolent political action or civil resistance has also been central to toppling communist regimes in Eastern Europe and to pro-democracy popular movements in Serbia, Georgia and the Ukraine. By scrutinizing the theories behind nonviolence, such as the role of the state, the rule of law and the nature of social and political power, Atack establishes nonviolence as a credible theme within Western political thought -- Publisher's description.